Fabrication of Au/graphene oxide/Ag sandwich structure thin film and its tunable energetics and tailorable optical properties - Hong, Ruijin (2018)
Au/graphene oxide/Ag sandwich structure thin film was fabricated. The effects of graphene oxide (GO) and bimetal on the structure and optical properties of metal silver films were investigated by X-ray diffraction (XRD), optical absorption, and Raman intensity measurements, respectively. Compared to silver thin film, Au/graphene oxide/Ag sandwich structure composite thin films were observed with wider optical absorption peak and enhanced absorption intensity. The Raman signal for Rhodamine B molecules based on the Au/graphene oxide/Ag sandwich nanostructure substrate were obviously enhanced due to the bimetal layer and GO layer with tunable absorption intensity and fluorescence quenching effects.